If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4) * 8 = 16 Reorder the terms: (-4 + x) * 8 = 16 Reorder the terms for easier multiplication: 8(-4 + x) = 16 (-4 * 8 + x * 8) = 16 (-32 + 8x) = 16 Solving -32 + 8x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 8x = 16 + 32 Combine like terms: -32 + 32 = 0 0 + 8x = 16 + 32 8x = 16 + 32 Combine like terms: 16 + 32 = 48 8x = 48 Divide each side by '8'. x = 6 Simplifying x = 6
| 3f+5=17 | | x=22-3.5x | | 5x-5=8-7x | | 9x-(2x+7)=3x-43 | | 0=250-9x-x^2+112 | | 2tanx=0 | | x+7x-44=0 | | 23/4+6= | | (15-0.5p)(p-2)=10 | | .5(x+2)-.2(x-8)=0 | | x^2+x+5=x+10 | | 3.5+.75= | | 5x-3x=-1-4 | | (x)+(x+1)=19 | | 31/2+3/4= | | 2(3y+2)=5(2y-4) | | P=a+b+3c | | 4a+3=9 | | 12x+1=57x+40 | | -4-3x=3x+14 | | 2(19)+2(79)= | | (3x-1)(2-x)-x(x+3)=2 | | 9-7x=20+4x | | 5hm=h+28k | | 4z+10-2z=6+z+8 | | x(2x+7)-5=(x+4)(5-x) | | 6x^2+27x-15=0 | | x+y=85 | | 5/9(F-32)= | | (4.6)(-2.25)= | | A=7+3x(5+49*7) | | 6n+8=3n+36 |